The Influence of Compensation and Career Development on Employees' Organizational Commitment in Class III UPBU Offices in the Merauke Region - Endah Iswahyuni Rina Astuti; Nurmala Pangaribuan; Elly Noer (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This quantitative research with a causality analysis approach investigates the effects of compensation, career development, and job satisfaction on organizational commitment. A sample of 148 Class III UPBU office employees in the Merauke region participated. Data was collected through questionnaires on a 5-point Likert scale and analyzed using path analysis. The results showed that compensation positively affects job satisfaction but not directly impact organizational commitment. Career development was also found to have a positive effect on both job satisfaction and organizational commitment. Finally, job satisfaction was positively linked to organizational commitment and mediated the relationship between compensation/career development and organizational commitment.